Research progress on m6A and drug resistance in gastrointestinal tumors - Xu, Ziyi; Sun, Bo; Wang, Weizheng; Fan, Yitao; Su, Jingxiang; Sun, Jiachun; Gu, Xinyu (Frontiers in Pharmacology, 2025)
Gastrointestinal (GI) tumors represent a significant global health burden and are among the leading causes of cancer-related mortality worldwide. their drug resistance is one of the major challenges in cancer therapy. In recent years, epigenetic modifications, especially N6-methyladenosine (m6A) RNA modifications, have become a hot research topic. m6A modification plays an important role in gene expression and cancer progression by regulating RNA splicing, translation, stability, and degradation, which are regulated by “writers,” “erasers” and “readers.” In GI tumors, resistance to chemotherapy, targeted therapy, and immunotherapy is closely associated with m6A RNA modification. Therefore, the molecular mechanism of m6A modification and its targeted drug development provide new therapeutic strategies for overcoming drug resistance and therapeutic efficacy in GI tumors. In this review, the biological functions of m6A were explored, the specific resistance mechanisms of m6A in different types of GI tumors were explored, new ideas and targets for future treatment resistance were identified, and the limitations of this field were highlighted.